The Effects of Age and Body Mass Index on Blood Glucose, Blood Cholesterol, and Blood Pressure in Adult Women - Riza Fikriana (Indian Journal of Public Health Research & Development, 2018)
Introduction: The risk factors of cardiovascular disease include having a high body mass index,hyperglycemia, hypercholesterolemia and increased blood pressure. The purpose of this study was to analyse the effects of age and body mass index (BMI) on blood glucose, blood cholesterol and blood pressure in adult women. Method: An analytical observation using a cross-sectional method was employed as the study design. The study recruited 60 women aged between 30 to 60 years old to participate, using a purposive sampling technique. The data was analysed using univariate analysis and path analysis. Result: Age and BMI showed as having the strongest direct effect on the blood pressure. Age also had a direct effect on blood glucose level and blood cholesterol level. The effect of age on blood glucose and blood cholesterol was also mediated by BMI. Conclusion: Being of an older age had a direct effect on increased blood glucose, blood cholesterol, and blood pressure, while a higher BMI had a direct effect on increased blood pressure. As women get older, maintaining a normal BMI is beneficial to preventing the increase of their blood glucose, blood cholesterol and blood pressure.